Marathon-induced cardiac strain as model for the evaluation of diagnostic micrornas for acute myocardial infarction - Shirvani Samani, Omid; Scherr, Johannes; Kayvanpour, Elham; Haas, Jan; Lehmann, David H.; Gi, Weng-Tein; Frese, Karen S.; Nietsch, Rouven; Fehlmann, Tobias; Sandke, Steffi; Weis, Tanja; Keller, Andreas; et al. (Journal of Clinical Medicine, 2022)
Background: The current gold standard biomarker for myocardial infarction (MI), cardiac troponin (cTn), is recognized for its high sensitivity and organ specificity; however, it lacks diagnostic specificity. Numerous studies have introduced circulating microRNAs as potential bi-omarkers for MI. This study investigates the MI-specificity of these serum microRNAs by investi-gating myocardial stress/injury due to strenuous exercise. Methods: MicroRNA biomarkers were retrieved by comprehensive review of 109 publications on diagnostic serum microRNAs for MI. MicroRNA levels were first measured by next-generation sequencing in pooled sera from runners (n = 46) before and after conducting a full competitive marathon. Hereafter, reverse transcription quantitative real-time PCR (qPCR) of 10 selected serum microRNAs in 210 marathon runners was performed (>10,000 qPCR measurements). Results: 27 potential diagnostic microRNA for MI were retrieved by the literature review. Eight microRNAs (miR-1-3p, miR-21-5p, miR-26a-5p, miR-122-5p, miR-133a-3p, miR-142-5p, miR-191-5p, miR-486-3p) showed positive correlations with cTnT in marathon runners, whereas two miRNAs (miR-134-5p and miR-499a-5p) showed no correlations. Upregulation of miR-133a-3p (p = 0.03) and miR-142-5p (p = 0.01) went along with elevated cTnT after marathon. Conclusion: Some MI-associated microRNAs (e.g., miR-133a-3p and miR-142-5p) have similar kinetics under strenuous exercise and MI as compared to cTnT, which suggests that their diagnostic specificity could be limited. In contrast, several MI-associated microRNAs (miR-26a-5p, miR-134-5p, miR-191-5p) showed different release behavior; hence, combining cTnT with these microRNAs within a multi-marker strategy may add diagnostic accuracy in MI.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biomarker; Exercise; Marathon running; MicroRNAs; Myocardial infarction; Troponin